Transcranial direct current stimulation (tDCS). An effective tool for improving episodic memory in young people? - Fernández, Alba; Cid-Fernández, Susana; Díaz, Fernando (Anales de Psicología / Annals of Psychology, 2021)
The main aim of the present study was to determine the effects of anodal vs sham tDCS administered over the dlPFC during the encoding phase of an episodic memory task, on the accuracy rate (AR) and reaction time (RT) measured in the immediate and delayed recall phases of the task, in a group of 23 healthy young participants. A randomized double-blind sham-controlled study of tDCS was carried out. The results evidenced significant main effects for factors Block, Session, and Delay on the AR and on RT, but not for the Group factor. Robust intra-session and inter-session learning effects but no Group (anodal vs sham tDCS) effect in episodic memory performance or in pre-post intervention neuropsychological tests were found. However, participants who received anodal tDCS showed shorter RT in the 24 hours delay interval and maintained it one week later, while those who received sham tDCS did not show the 24 hours RT shortening and even showed a RT increase one week later. These results could indicate a subtle modulatory effect of anodal tDCS on memory decay along delay intervals. The experimental protocol showed its potential utility to be used in samples of healthy elderly or mild cognitive impairment participants